The rainbow eaudiobook - Lawrence, D. H. (Tantor Media, 2010)
Set in the rural midlands of England, The Rainbow revolves around three generations of the Brangwen family over a period of more than sixty years, setting them against the emergence of modern England. When Tom Brangwen marries a Polish widow and adopts her daughter as his own, he is unprepared for the conflict and passion that erupt. Suffused with biblical imagery, The Rainbow addresses searching human issues in a setting of precise and vivid detail. In The Rainbow , D. H. Lawrence challenged the customary limitations of language and convention to carry into the structures of his prose the fascination with boundaries and space that characterize the entire novel. A visionary novel, considered to be one of Lawrence's finest, it explores the complex sexual and psychological relationships between men and women in an increasingly industrialized world.